Gene expression patterns of helicoverpa armigera gut proteases - Chougule, Nanasaheb P.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Insect Biochemistry and Molecular Biology, 2005)
Relative quantification of reported gut proteinase cDNAs from Helicoverpa armigera larvae fed on various host plants (cotton, chickpea, pigeonpea, tomato and okra), non-host plant Pis (winged bean, bitter gourd, ground nut, and capsicum) and during larval development has been carried out using semi-quantitative RT-PCR. Five trypsin-like and three chymotrypsin-like proteinases were categorized as insensitive or sensitive to most of the proteinase inhibitors (Pis) and insensitive/sensitive to specific Pis based on their expression analysis. These results were supported by amino acid sequence analysis, where diverged amino acids were observed in the regions, which are reported to be involved in typical trypsin trypsin inhibitor interactions and critical for proteinase inhibitor resistance. Among exopeptidases (five aminopeptidase and three carboxypeptidase), HaAmi4 and HaAmi5 of aminopeptidase and HaCar1 of carboxypeptidase exhibited considerable differential expression. Elastase and cathepsin B-like proteinases were expressed at negligible levels. The proteases identified in the study would be ideal candidates for further interactions studies with protease inhibitors to understand the structural reasons of protease inhibitor insensitivity (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: expression; gut proteinases; Helicoverpa armigera; Proteinase inhibitors; RT-PCR

Higher accumulation of proteinase inhibitors in flowers than leaves and fruits as a possible basis for differential feeding preference of Helicoverpa armigera on tomato (Lycopersicon esculentum Mill, Cv. Dhanashree) - Damle, M. S.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Phytochemistry, 2005)
Tomato (Lycopersicon esculentum, Mill; cultivar- Dhanashree) proteinase inhibitors (Pis) were tested for their trypsin inhibitory (TT) and Helicoverpa armigera gut proteinases inhibitory (HGPI) activity in different organs of the tomato plants. Analysis of TI and HGPI distribution in various parts of the plant showed that flowers accumulated about 300 and 1000 times higher levels of TI while 700 and 400 times higher levels of HGPI as compared to those in leaves and fruits, respectively. Field observation that H. armigera larvae infest leaves and fruits but not the flowers could be at least partially attributed to the protective role-played by the higher levels of Pis in the flower tissue. Tomato Pis inhibited about 50-80% HGP activity of H. armigera larvae feeding on various host plants including tomato, of larvae exposed to non-host plant Pis and of various larval instars. Tomato Pis were found to be highly stable to insect proteinases wherein incubation of inhibitor with HGP even for 3 h at optimum conditions did not affect inhibitory activity. Bioassay using H. armigera larvae fed on artificial diet containing tomato PIs revealed adverse effect on larval growth, pupae development, adult formation and fecundity. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: accumulation of PI; Helicoverpa armigera; Lycopersicon esculentum; Midgut proteinases; Plant defense; Proteinase inhibitors

In vivo and in vitro effect of capsicum annum proteinase inhibitors on helicoverpa armigera gut proteinases - Tamhane, V. A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Dixit, A. R.; Sainani, Mohini N.; Gupta, Vidya S. (Biochimica Et Biophysica Acta-General Subjects, 2005)
Two proteinase inhibitors (PIs), CapA1 and CapA2, were purified from Capsicum annum Linn. Var. Phule Jyoti leaves and assessed for their in vitro and in vivo activity against Helicoverpa armigera gut proteinases (HGPs). Both the inhibitors exhibited molecular weights of about 12 kDa with inhibitory activity against bovine trypsin and chymotrypsin indicating presence of probable two-inhibitor repeats of PIN II family. CapA1 and CapA2 inhibited 60-80% HGP (azocaseinolytic) activity of fourth instar larvae feeding on various host plants while 45-65% inhibition of HGP activity of various instars (II to VI) larvae reared on artificial diet. The partial purification of HGP isoforms, their characterization with synthetic inhibitors and inhibition by C. annum PIs revealed that most of the trypsin-like activity (68-91%) of HGPs was sensitive to C. annum PIs while 39-85% chymotrypsin-like activity of HGPs was insensitive to these inhibitors. The feeding of C. annum leaf extracts and two purified PIs in various doses to H. armigera larvae for two successive generations through artificial diet demonstrated their potential in inhibiting larval growth and development, delay in pupation period and dramatic reduction in fecundity and fertility. This is the first report-demonstrating efficacy of C. annum PIs against insect gut proteinases as well as larval growth and development of H. armigera. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Capsicum annum; gut proteinase; Helicoverpa armigera; insect resistance; Proteinase inhibitor

Kunitz trypsin inhibitor from chickpea (Cicer arietinum L.) that exerts anti-metabolic effect on podborer (Helicoverpa armigera) larvae - Srinivasan, A.; Giri, Ashok P.; Harsulkar, Abhay M.; Gatehouse, J. A.; Gupta, Vidya S. (Plant Molecular Biology, 2005)
Chickpea (Cicer arietinum L.) seeds contain Bowman-Birk proteinase inhibitors, which are ineffective against the digestive proteinases of larvae of the insect pest Helicoverpa armigera. We have identified and purified a low expressing proteinase inhibitor (PI), distinct from the Bowman-Birk Inhibitors and active against H. armigera gut proteinases (HGP), from chickpea seeds. N-terminal sequencing of this HGP inhibitor revealed a sequence similar to reported pea (Pisum sativum) and chickpea alpha-L-fucosidases and also homologous to legume Kunitz inhibitors. The identity was confirmed by matrix assisted laser desorption ionization - time of flight analysis of tryptic peptides and isolation of DNA sequence coding for the mature protein. Available sequence data showed that this protein forms a distinct phylogenetic cluster with Kunitz inhibitors from Glycine max, Medicago truncatula, P. sativum and Canavalia lineata. The isolated coding sequence was cloned into a yeast expression vector and produced as a recombinant protein in Pichia pastoris. alpha-L-fucosidase activity was not detectable in purified or recombinant protein, by solution assays. The recombinant protein did not inhibit chymotrypsin or subtilisin activity but did exhibit stoichiometric inhibition of trypsin, comparable to soybean Kunitz trypsin inhibitor. The recombinant protein exhibited higher inhibition of total HGP activity as compared to soybean kunitz inhibitor, even though it preferentially inhibited HGP-trypsins. H. armigera larvae fed on inhibitor-incorporated artificial diet showed significant reduction in average larval weight after 18 days of feeding demonstrating potent antimetabolic activity. The over-expression of this gene in chickpea could act as an endogenous source of resistance to H. armigera.
Keywords: Chickpea; Cicer arietinum; fucosidase; Helicoverpa armigera; Kunitz; Proteinase inhibitor

Podborer (Helicoverpa armigera Hubn.) does not show specific adaptations in gut proteinases to dietary Cicer arietinum Kunitz proteinase inhibitor - Srinivasan, A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Gatehouse, J. A.; Gupta, Vidya S. (Journal of Insect Physiology, 2005)
We investigated the response of Helicoverpa armigera larvae towards ingestion of Cicer arietinum Kunitz proteinase inhibitor (CaKPI), which caused antagonistic effects on developing H. armigera larvae. CaKPI-degrading proteinases were not detectable in either control or sensitized larvae. There were negligible increases in total proteinase activity, as well as in trypsin-like and chymotrypsin-like activities of H. armigera gut proteinases (HGPs). Decrease in sensitivity of HGPs to inhibition by CaKPI was not observed when the inhibitor was fed Suggesting that the insect had not shown a specific adaptive response to dietary CaKPI. Semi-quantitative reverse transcriptase polymerase chain reaction (Q RT-PCR) analysis showed a general up-regulation of proteases in larvae that ingested CaKPI and a specific regulation of individual transcripts was not observed. CaKPI had maximum inhibitory activity against HGP derived from fourth instar larvae. CaKPI was equally potent in inhibition of HGPs derived from larvae fed on different host plants, as well as various proteinase inhibitors (Pis) to which larval adaptation was previously reported. The lack of larval response to CaKPI was attributable to the atypical active site sequence and inhibitory activity of CaKPI and/or to the pre-adaptation of H. armigera larvae due to the constant exposure to basal levels of CaKPI in chickpea seeds or a chickpea seed-based diet. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cicer arietinum; Helicoverpa armigera; insect response; proteinase; Proteinase inhibitor

Assimilatory potential of helicoverpa armigera reared on host (chickpea) and nonhost (cassia tora) diets - Dawkar, Vishal V.; Chikate, Yojana R.; Gupta, Vidya S.; Slade, Susan E.; Giri, Ashok P. (Journal of Proteome Research, 2011)
Adaptation to plant allelochemicals is a crucial aspect of herbivore chemical ecology. To understand an insect ecology, we studied an effect of nonhost Cassia tora seed-based diet (Ct) on growth, development, and molecular responses in Helicoverpa armigera. We employed a comparative approach to investigate the proteomic differences in gut, hemolymph, and frass of H. armigera reared on a normal (chickpea seed-based, Cp) and Ct diet. In this study, a total of 46 proteins were identified by nano-LC-MS(E). Among them, 17 proteins were up-regulated and 29 proteins were down-regulated when larvae were exposed to the Ct diet. Database searches combined with GO analysis revealed that gut proteases engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification were down-regulated in the Ct fed larvae. Proteins identified in H. armigera hemolymph were found to be involved in defense mechanisms. Moreover, proteins found in frass of the Ct fed larvae were observed to participate in energy metabolism. Biochemical and quantitative real-time PCR analysis of selected candidate proteins showed differential gene expression patterns and corroborated with the proteomic data. Our results suggest that the Ct diet could alter expression of proteins related to digestion, absorption of nutrients, adaptation, defense mechanisms, and energy metabolism in H. armigera.
Keywords: adaptation; Cassia tora; Gene expression; Helicoverpa armigera; proteomics

Amylase gene expression patterns in Helicoverpa armigera upon feeding on a range of host plants - Kotkar, Hemlata M.; Bhide, Amey J.; Gupta, Vidya S.; Giri, Ashok P. (Gene, 2012)
Expression of two amylase genes (HaAmy1 and HaAmy2) was studied in Helicoverpa armigera (Hubner; Lepidoptera: Noctuidae) feeding on different host plants and during larval development. Alignment of HaAmy1 and HaAmy2 with other insect amylases shows similarities with known Lepidopteran amylase transcripts. H. armigera amylase gene expression is influenced by the availability of reducing sugars, sucrose and starch content of host plants and further correlates to the pool of reducing sugars in the gut and haemolymph of larvae. HaAmy1 and HaAmy2 during larval development on two host plants viz., maize (cereal) and marigold (ornamental) showed their relative difference. Results support the view that when host plants differ in their macronutrients, relationships of enzymes and substrates are flexible. The present work highlights the distribution of HaAmy1 and HaAmy2 (i) during various stages of insect development (second, fourth and sixth instar, pupa, adult and egg), (ii) in various tissues viz., head, haemolymph, fat body, integument and whole larval body of H. armigera feeding on artificial diet and (iii) in three gut regions of larvae fed on various diets. Complexity in expression of amylase genes suggests existence of mechanisms involved to detect nutrient balance required for avoiding fitness costs and focus their importance in insect nutrition. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Diets; Digestive amylase; Gene expression; Helicoverpa armigera; Nutrition

Differential protease activity augments polyphagy in helicoverpa armigera - Chikate, Yojana R.; Tamhane, V. A.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Insect Molecular Biology, 2013)
Helicoverpa armigera (Lepidoptera: Noctuidae) and other polyphagous agricultural pests are extending their plant host range and emerging as serious agents in restraining crop productivity. Dynamic regulation, coupled with a diversity of digestive and detoxifying enzymes, play a crucial role in the adaptation of polyphagous insects. To investigate the functional intricacy of serine proteases in the development and polyphagy of H.armigera, we profiled the expression of eight trypsin-like and four chymotrypsin-like phylogenetically diverse mRNAs from different life stages of H.armigera reared on nutritionally distinct host plants. These analyses revealed diet- and stage-specific protease expression patterns. The trypsins expressed showed structural variations, which might result in differential substrate specificity and interaction with inhibitors. Protease profiles in the presence of inhibitors and their mass spectrometric analyses revealed insight into their differential activity. These findings emphasize the differential expression of serine proteases and their consequences for digestive physiology in promoting polyphagy in H.armigera.
Keywords: adaptation; chymotrypsin; Helicoverpa armigera; polyphagy; Trypsin

Differential antibiosis against helicoverpa armigera exerted by distinct inhibitory repeat domains of capsicum annuum proteinase inhibitors - Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Phytochemistry, 2014)
Plant defensive serine proteinase inhibitors (Pis) are known to have negative impact on digestive physiology of herbivore insects and thus have a crucial role in plant protection. Here, we have assessed the efficacy and specificity of three previously characterized inhibitory repeat domain (IRD) variants from Capsicum annuum PIs viz., IRD-7, -9 and -12 against gut proteinases from Helicoverpa armigera. Comparative study of in silico binding energy revealed that IRD-9 possesses higher affinity towards H. armigera serine proteinases as compared to IRD-7 and -12. H. armigera fed on artificial diet containing 5 TIU/g of recombinant IRD proteins exhibited differential effects on larval growth, survival rate and other nutritional parameters. Major digestive gut trypsin and chymotrypsin genes were down regulated in the IRD fed larvae, while few of them were up-regulated, this indicate alterations in insect digestive physiology. The results corroborated with proteinase activity assays and zymography. These findings suggest that the sequence variations among Pis reflect in their efficacy against proteinases in vitro and in vivo, which also could be used for developing tailor-made multi-domain inhibitor gene(s). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Capsicum annuum; Helicoverpa armigera; Inhibitory repeat domain; Proteases; Proteinase inhibitors

Identification and expression profiling of helicoverpa armigera microRNAs and their possible role in the regulation of digestive protease genes - Lomate, Purushottam R.; Mahajan, Neha S.; Kale, Sandip M.; Gupta, Vidya S.; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2014)
The present investigation is an effort to determine the possible roles of microRNAs (miRNAs) in the regulation of protease gene expression in Helicoverpa armigera upon exposure to plant protease inhibitors (PIs). Using Illumina platform, deep sequencing of 12 small RNA libraries was performed from H. armigera larvae fed on artificial diet (AD) or recombinant Capsicum annuum PI-7 (rCanPI-7) incorporated diet, at various time intervals (0.5, 2, 6, 12, 24, and 48 h). Sequencing data were analyzed with miRDeep2 software; a total of 186 unique miRNAs were identified from all the 12 libraries, out of which 96 were conserved while 90 were novel. These miRNAs showed all the conserved characteristics of insect miRNAs. Homology analysis revealed that most of the identified miRNAs were insect-specific, and more than 50 miRNAs were Lepidoptera-specific. Several candidate miRNAs (conserved and novel) were differentially expressed in rCanPI-7 fed larvae as compared to the larvae fed on AD. H. armigera miRNAs were found to have target sites in several protease genes as well as in protease regulation related genes such as serine PI and immune reactive PI. As expected, negative correlation in the relative abundance miRNAs and their target mRNAs was evident from qualitative real time polymerase chain reaction analysis. The investigation revealed potential roles of miRNAs in H. armigera protease gene regulation. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Deep sequencing; Helicoverpa armigera; miRNAs; Protease gene regulation; Protease inhibitors

Remarkable efficiency of a pin-II proteinase inhibitor sans two conserved disulfide bonds is due to enhanced flexibility and hydrogen bond density in the reactive site loop - Joshi, Rakesh S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Ghosh, Anirban; Sonavane, Uddhavesh; Suresh, C. G.; Joshi, Rajendra; Gupta, Vidya S.; Giri, Ashok P. (Journal of Biomolecular Structure & Dynamics, 2014)
Capsicum annuum (L.) expresses diverse potato type II family proteinase inhibitors comprising of inhibitory repeat domain (IRD) as basic functional unit. Most IRDs contain eight conserved cysteines forming four disulfide bonds, which are indispensible for their stability and activity. We investigated the functional significance of evolutionary variations in IRDs and their role in mediating interaction between the inhibitor and cognate proteinase. Among the 18 IRDs encoded by C. annuum, IRD-7, -9, and -12 were selected for further characterization on the basis of variation in their reactive site loop, number of conserved cysteine residues, and higher theoretical G(bind) for interaction with Helicoverpa armigera trypsin. Moreover, inhibition kinetics showed that IRD-9, despite loss of some of the disulfide bonds, was a more potent proteinase inhibitor among the three selected IRDs. Molecular dynamic simulations revealed that serine residues in the place of cysteines at seventh and eighth positions of IRD-9 resulted in an increase in the density of intramolecular hydrogen bonds and reactive site loop flexibility. Results of the serine residues chemical modification also supported this observation and provided a possible explanation for the remarkable inhibitory potential of IRD-9. Furthermore, this natural variant among IRDs showed special attributes like stability to proteolysis and synergistic inhibitory effect on other IRDs. It is likely that IRDs have coevolved selective specialization of their structure and function as a response towards specific insect proteases they encountered. Understanding the molecular mechanism of pest protease-plant proteinaceous inhibitor interaction will help in developing effective pest control strategies.An animated interactive 3D complement (I3DC) is available in Proteopedia at http://proteopedia.org/w/Journal:JBSD:39
Keywords: Capsicum annuum; Helicoverpa armigera; Proteases; Proteinase inhibitor

Way toward ``dietary pesticides'': molecular investigation of insecticidal action of caffeic acid against helicoverpa armigera - Joshi, Rakesh S.; Wagh, T. P.; Sharma, N.; Mulani, Fayaj A.; Sonavane, U.; Thulasiram, H. V.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Agricultural and Food Chemistry, 2014)
Bioprospecting of natural molecules is essential to overcome serious environmental issues and pesticide resistance in insects. Here we are reporting insights into insecticidal activity of a plant natural phenol. In silico and in vitro screening of multiple molecules supported by in vivo validations suggested that caffeic acid (CA) is a potent inhibitor of Helicoverpa armigera gut proteases. Protease activity and gene expression were altered in CA-fed larvae. The structure-activity relationship of CA highlighted that all the functional groups are crucial for inhibition of protease activity. Biophysical studies and molecular dynamic simulations revealed that sequential binding of multiple CA molecules induces conformational changes in the protease(s) and thus lead to a significant decline in their activity. CA treatment significantly inhibits the insect's detoxification enzymes, thus intensifying the insecticidal effect. Our findings suggest that CA can be implicated as a potent insecticidal molecule and explored for the development of effective dietary pesticides.
Keywords: Caffeic acid; Helicoverpa armigera; insecticidal activity; protease inhibitor

Biochemical, structural and functional diversity between two digestive alpha-amylases from helicoverpa armigera - Bhide, Amey J.; Channale, Sonal M.; Patil, Sucheta S.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2015)
Background: Helicoverpa armigera (Lepidoptera) feeds on various plants using diverse digestive enzymes as one of the survival tool-kit. The aim of the present study was to understand biochemical properties of recombinant alpha-amylases of H. armigera viz., HaAmy1 and HaAmy2. Methods: The open reading frames of HaAmy1 and HaAmy2 were cloned in Pichia pastoris and expressed heterologously. Purified recombinant enzymes were characterized for their biochemical and biophysical attributes using established methods. Results: Sequence alignment and homology modeling showed that HaAmy1 and HaAmy2 were conserved in their amino acid sequences and structures. HaAmy1 and HaAmy2 showed optimum activity at 60 degrees C; however, they differed in their optimum pH. Furthermore, HaAmy2 showed higher affinity for starch and amylopectin whereas HaAmy1 had higher catalytic efficiency. HaAmy1 and HaAmy2 were inhibited to the same magnitude by a synthetic amylase inhibitor (acarbose) while wheat amylase inhibitor showed about 2-fold higher inhibition of HaAmy1 than HaAmy2 at pH 7 while 6-fold difference at pH 11. Interactions of HaAmy1 and HaAmy2 with wheat amylase inhibitor revealed 2:1 stoichiometric ratio and much more complex interaction with HaAmy1. Conclusions: The diversity of amylases in perspective of their biochemical and biophysical properties, and their differential interactions with amylase inhibitors signify the potential role of these enzymes in adaptation of H. armigera on diverse plant diets. General significance: Characterization of digestive enzymes of H. armigera provides the molecular basis for the polyphagous nature and thus could assist in designing future strategies for the insect control. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: alpha-amylases; Amylase inhibitors; Digestive enzymes; Enzyme activity; Helicoverpa armigera

Expression of proteins involved in digestion and detoxification are regulated in helicoverpa armigera to cope up with chlorpyrifos insecticide - Dawkar, Vishal V.; Chikate, Yojana R.; More, Tushar H.; Gupta, Vidya S.; Giri, Ashok P. (Insect Science, 2016)
Helicoverpa armigera is a key pest in many vital crops, which is mainly controlled by chemical strategies. To manage this pest is becoming challenging due to its ability and evolution of resistance against insecticides. Further, its subsequent spread on nonhost plant is remarkable in recent times. Hence, decoding resistance mechanism against phytochemicals and synthetic insecticides is a major challenge. The present work describes that the digestion, defense and immunity related enzymes are associated with chlorpyrifos resistance in H. armigera. Proteomic analysis of H. armigera gut tissue upon feeding on chlorpyrifos containing diet (CH) and artificial diet (AD) using nano-liquid chromatography-mass spectrometry identified upregulated 23-proteins in CH fed larvae. Database searches combined with gene ontology analysis revealed that the identified gut proteins engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification. Biochemical and quantitative real-time polymerase chain reaction analysis of candidate proteins indicated that insects were struggling to get nutrients and energy in presence of CH, while at the same time endeavoring to metabolize chlorpyrifos. Moreover, we proposed a potential processing pathway of chlorpyrifos in H. armigera gut by examining the metabolites using gas chromatography-mass spectrometry. H. armigera exhibit a range of intriguing behavioral, morphological adaptations and resistance to insecticides by regulating expression of proteins involved in digestion and detoxification mechanisms to cope up with chlorpyrifos. In these contexts, as gut is a rich repository of biological information; profound analysis of gut tissues can give clues of detoxification and resistance mechanism in insects.
Keywords: chlorpyrifos; Helicoverpa armigera; insecticide resistance; proteomics; real-time PCR

Tripeptides derived from reactive centre loop of potato type II protease inhibitors preferentially inhibit midgut proteases of Helicoverpa armigera - Saikhedkar, Nidhi S.; Joshi, Rakesh S.; Bhoite, Ashwini S.; Mohandasan, Radhika; Yadav, Amit Kumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2018)
Potato type II protease inhibitors (Pin-II PIs) impede the growth of lepidopteran insects by inhibiting serine protease-like enzymes in the larval gut. The three amino acid reactive centre loop (RCL) of these proteinaceous inhibitors is crucial for protease binding and is conserved across the Pin-II family. However, the molecular mechanism and inhibitory potential of the RCL tripeptides in isolation of the native protein has remained elusive. In this study, six peptides corresponding to the RCLs of the predominant Pin-II PIs were identified, synthesized and evaluated for in vitro and in vivo inhibitory activity against serine proteases of the polyphagous insect, Helicoverpa armigera. RCL peptides with sequences PRN, PRY and TRE were found to be potent inhibitors that adversely affected the growth and development of H. armigera. The binding mechanism and differential affinity of the RCL peptides with serine proteases was delineated by crystal structures of complexes of the RCL peptides with trypsin. Residues P1 and P2 of the inhibitors play a crucial role in the interaction and specificity of these inhibitors. Important features of RCL peptides like higher inhibition of insect proteases, enhanced efficacy at alkaline gut pH, longer retention and high stability in insect gut make them suitable molecules for the development of sustainable pest management strategies for crop protection.
Keywords: Helicoverpa armigera; Protease; protease inhibitor; Reactive centre loop peptides

NMR structure and dynamics of inhibitory repeat domain variant 12, a plant protease inhibitor from Capsicum annuum, and its structural relationship to other plant protease inhibitors - Gartia, Janeka; Anangi, Raveendra; Joshi, Rakesh S.; Giri, Ashok P.; King, Glenn F.; Barnwal, Ravi P.; Chary, Kandala V. R. (Journal of Biomolecular Structure & Dynamics, 2019)
Although several plant protease inhibitors have been structurally characterized using X-ray crystallography, very few have been studied using NMR techniques. Here, we report an NMR study of the solution structure and dynamics of an inhibitory repeat domain (IRD) variant 12 from the wound-inducible Pin-II type proteinase inhibitor from Capsicum annuum. IRD variant 12 (IRD12) showed strong anti-metabolic activity against the Lepidopteran insect pest, Helicoverpa armigera. The NMR-derived three-dimensional structure of IRD12 reveals a three-stranded anti-parallel beta-sheet rigidly held together by four disulfide bridges and shows structural homology with known IRDs. It is interesting to note that the IRD12 structure containing similar to 75% unstructured part still shows substantial amount of rigidity of N-H bond vectors with respect to its molecular motion. Communicated by Ramaswamy H. Sarma
Keywords: Bt transgenic; Capsicum annuum; Helicoverpa armigera; inhibitory repeating domains; NMR structure; Protease inhibitors (PIs)

Aminoacylase efficiently hydrolyses fatty acid amino acid conjugates of Helicoverpa armigera potentially to increase the pool of glutamine - Kallure, Gopal S.; Sahoo, Shubhranshu Shekhar; Kale, Rutuja S.; Barvkar, Vitthal T.; Kontham, Ravindar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2024)
One of the most prevalent bioactive molecules present in the oral secretion (OS) of lepidopteran insects is fatty acid amino acid conjugates (FACs). Insect dietary components have influence on the synthesis and retaining the pool of FACs in the OS. We noted differential and diet-specific accumulation of FACs in the OS of Helicoverpa armigera by using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Interestingly, we identified FACs hydrolyzing enzyme aminoacylase (HaACY) in the OS of H. armigera through proteomic analysis. Next, we have cloned, expressed, and purified active recombinant HaACY in the bacterial system. Recombinant HaACY hydrolyzes all the six identified FACs in the OS of H. armigera larvae fed on host and non-host plants and releases respective fatty acid and glutamine. In these six FACs, fatty acid moieties vary while amino acid glutamine was common. Glutamine obtained upon hydrolysis of FACs by HaACY might serve as an amino acid pool for insect growth and development. To understand the substrate choices of HaACY, we chemically synthesized, purified, and characterized all the six FACs. Interestingly, rHaACY also shows hydrolysis of synthetic FACs into respective fatty acid and glutamine. Our results underline the importance of diet on accumulation of FACs and role of aminoacylase(s) in regulating the level of FACs and glutamine.
Keywords: Aminoacylase; Fatty acid amino acid conjugates; Glutamine; Helicoverpa armigera; Oral secretion